ANALYSIS OF PAYROLL ACCOUNTING SYSTEM AT CV. SYARIAH MOBILINDO - Ari Kharisma (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the existing Payroll Accounting Information System at CV. Syariah Mobilindo Gunung Sindur Branch. The research method used is qualitative, based on primary data obtained through interviews and documentation. The analysis was conducted using flowcharts to illustrate the existing processes. The results of the study indicate that there is a duplication of tasks in the finance department. The recommendation provided for CV. Syariah Mobilindo Gunung Sindur Branch is to add functions to the Accounting Department to separate responsibilities between departments according to their authority and duties. The addition of documents in the form of Employee Attendance Records (EAR) to the commissioner's department to prevent misuse of attendance, and the addition of Payroll Reports (PR) to the accounting department as accountability to the Director.